LEADERSHIP, LEARNING, AND CULTURE: HOW PRINCIPAL LEADERSHIP AND TEACHER EDUCATION DRIVE PERFORMANCE THROUGH ORGANIZATIONAL CULTURE - Maisusiyanti; Kristina Sedyastuti; Adi Suroso (SOSIOEDUKASI, 2026)
This study aims to examine the influence of principal leadership and teacher educational background on teacher performance, with organizational culture as a mediating variable at SMKN 1 Batu, a Center of Excellence Vocational High School. A quantitative approach with an explanatory design was employed. The sample consisted of 52 teachers selected through total sampling. Data were collected using structured questionnaires with a Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that principal leadership, teacher educational background, and organizational culture each have a positive and significant direct effect on teacher performance, with organizational culture exhibiting the strongest influence. Furthermore, organizational culture serves as a significant mediator in the relationships between both principal leadership and teacher educational background on teacher performance. This study contributes a novel empirical insight by positioning organizational culture as a key mediating mechanism in the context of vocational education excellence, thereby offering practical implications for school leaders and policymakers. Specifically, strengthening leadership capacity, enhancing teacher qualifications, and fostering a collaborative school culture are essential strategies for achieving sustainable improvements in teacher performance.